Cross-breeding cattle for milk production in the tropics: achievements, challenges and opportunities - Galukande, E.; Mulindwa, H.; Wurzinger, Maria; Roschinky, R.; Okeyo Mwai, Ally; Sölkner, Johann (Cambridge University Press, 2013)
This paper reviews experiences with cross-breeding for milk production in the tropics. Data were compiled from 23 different studies evaluating the performance of different grades of cross-bred animals as well as local breeds. Relative performance of indigenous breeds compared with different grades of cross-breeds was calculated for three climatic zones. Traits considered were milk yield per lactation, age at first calving, services per conception, lifetime milk yield and total number of lactations completed. At 50 percent Bos taurus blood, lactation milk yields were 2.6, 2.4 and 2.2 times higher than those of local cattle in the highland, tropical wet and dry, and semi-arid climatic zones, respectively; lactation lengths increased by 1.2, 1.2 and 1.9 months in the above-mentioned climatic zones, respectively; there was a reduction in calving interval by 0.8 times and in age at first calving by 0.9 times. Similarly, cross-breds with 50 percent B. taurus genes had 1.8 times higher lifetime milk yields and a 1.2 times higher number of total lactations. Although cross-breeding faces a number of challenges such as better infrastructure, higher demand for health care, there are many advantages of using it. These are higher production per animal, higher income for the families and provision of high-value food. It is therefore likely to continue to be an important livestock improvement tool in the tropics in the future, where farmers can provide sufficient management for maintaining animals with higher input requirements and access to the milk market can be secured.